Determination of pore throat size in the sands of the Naricual Formation, traversed by the exploratory wells Sintu- 9, Ocre- 4X and Ocre-5, in the Sintu- Ocher, northern area of ​​Monagas, Venezuela (2010)
Starting from the obtained information of nuclei and conventional registrations, analysis petrográficos was made, Diffraction of Rays X (DRX), studies petrofísicos and special, (Electronic Microscopy of Sweeping and Capillary Pressure for Injection of Mercury). By means of the correlation of the graphics "one to one", was determined that the equation of Pittman 35 (R35), it is the one that better it is adjusted to it dates it of the nucleus SINTU - 9 and for the well OCRE - 5, the best correlation was represented by Winland 35. Later on the Type of Rock was characterized, obtaining stops the well SINTU - 9 rocks mainly mesoporosas and microporosas, on the other hand in the well OCRE - 5 the throats of pores vary between macroporosas and mesoporosas. Based on the obtained results it was determined that the good size for the particles densificantes was of 0,26 microns for the structural block of the well SINTU - 9 and a diameter of 1,21 microns for the block of the well OCRE - 5.